2010
DOI: 10.1002/met.230
|View full text |Cite
|
Sign up to set email alerts
|

Quality index scheme for quantitative uncertainty characterization of radar‐based precipitation

Abstract: A quality index scheme is proposed which is designed to evaluate the quality of different radar-derived rainfall products including processed radar data and precipitation accumulations. The idea of the quality index scheme is based on selection of quality factors, determination of their quality indices and computation of one final quality index. The factors were selected depending on the particular kind of precipitation field. In the proposed scheme the quality index for each quality factor is determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Friedrich et al, 2006;Szturc et al, 2011). The algorithm here presented is based mainly on already assessed techniques, but introduces also some new approaches.…”
mentioning
confidence: 99%
“…Friedrich et al, 2006;Szturc et al, 2011). The algorithm here presented is based mainly on already assessed techniques, but introduces also some new approaches.…”
mentioning
confidence: 99%
“…In order to investigate the error dependencies between radar and gauges, we use an indicator that describes the hy- drological aspects of the errors (Szturc et al, 2011), namely, the absolute difference between observed and analyzed precipitation accumulation as a function of the magnitude of the observed value (i.e. gauge data).…”
Section: Results and Verificationmentioning
confidence: 99%
“…Moreover non-precipitation echoes, such as ground clutter, are often characterized by high variability that differs from that for stratiform precipitation echoes. Spatial variability can be quantified as 3-D reflectivity gradient or standard deviation in a certain spatial grid (Szturc et al, 2011) and should be taken into account in quality index determination.…”
Section: Spatial Variability Of Reflectivity Fieldmentioning
confidence: 99%
“…However for some applications, such as flash flood prediction, more detailed quality information is expected by hydrologists (Sharif et al, 2004;Vivoni et al, 2007, Collier, 2009). A quality index approach for each radar pixel seems to be an appropriate way of quality characterization (Michelson et al, 2005;Friedrich et al, 2006;Szturc et al, 2006Szturc et al, , 2008aSzturc et al, , 2011. As a consequence a map of the quality index can be attached to the radar-based product.…”
mentioning
confidence: 99%